2005
DOI: 10.1007/s11270-005-7747-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Wood Ash and Green Liquor Dregs Application on Ca, Cu, Zn and Cd Contents in Bark and Wood of Norway Spruce

Abstract: To counteract nutrient depletion and acidification of forest soils, recycling of waste products from the forest industry has been suggested. Spreading of these waste products will probably change the concentration and availability of Ca and heavy metals in forest soils and thereby the contents of these metals in trees. This field study aimed at examining the influence of pellets of wood ash (ash) or a mixture of wood ash and green liquor dregs (ash+GLD) on the contents of Ca, Cd, Cu and Zn in wood and bark of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The Na and K salts in pulp mill residues are easily soluble, while Ca and Mg salts have limited solubility (Mahmoudkhani et al, 2004). GLD and lime mud also contain heavy metal constituents such as Cd, Cu and Zn, which are hazardous to the environment ( € Osterås et al, 2005). In Finland, an environmental permit is required for the use of the residues from Kraft mills as forest fertilizers.…”
Section: Fertilizers and Soil Amendmentsmentioning
confidence: 99%
“…The Na and K salts in pulp mill residues are easily soluble, while Ca and Mg salts have limited solubility (Mahmoudkhani et al, 2004). GLD and lime mud also contain heavy metal constituents such as Cd, Cu and Zn, which are hazardous to the environment ( € Osterås et al, 2005). In Finland, an environmental permit is required for the use of the residues from Kraft mills as forest fertilizers.…”
Section: Fertilizers and Soil Amendmentsmentioning
confidence: 99%
“…This might be because maize straw ash acted as a source of Mn. Increases in foliar Cu and Zn for biomass ash treatment have been reported by Osteras et al (2005). (24) .…”
mentioning
confidence: 88%
“…Increases in foliar Cu and Zn for biomass ash treatment have been reported by Osteras et al (2005). (24) . Available zinc content of the soil changed into double after the wood ash treatment (25) .…”
mentioning
confidence: 88%
“…Zambrano et al [50] showed that the physical and chemical characteristics of the waste are useful for plants, and the research confirmed their potential use on degraded soils in Chile. In Sweden, Österås et al [51] concluded that in a long-term perspective the use of such wastes does not increase the accumulation of heavy metals in plants. Lu et al [52] showed that the phytotoxicity is not a problem for land application in Taiwan.…”
Section: Green Liquor Dregsmentioning
confidence: 99%